Hearing Assistance Technology: Collaborating with Teens to Get It Right - Johnson, Cheryl DeConde (Seminars in Hearing, 2014)
The benefits of hearing assistance technology (HAT) to enhance speech and other desired auditory inputs for listeners with compromised auditory and listening skills are known. However, the best designed and fitted technology is only as effective as its utilization. Benefit is realized when the HAT device is used as prescribed, is used consistently, is working properly, and achieves the desired listening goals for the individual. Therefore, proper selection and management of HAT is critical to achieving the desired outcomes associated with HAT use. Even when benefit is demonstrated, and the HAT is well managed, there are other reasons why users opt not to use the devices. For teens, social identity and the desire to be like their peers complicate the use of HAT. Audiologists should do their part by collaborating with the HAT candidate to assure appropriate selection, fitting, counseling, and orientation and training procedures have occurred.
Keywords: Hearing assistance technology; classroom audio distribution system